2022
DOI: 10.1021/acs.chemmater.1c03815
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Halide Ordering as a Tool for the Stabilization of Ruddlesden–Popper Structures

Abstract: While the constraints on the choice of organic cations are greatly relaxed for layered two-dimensional perovskites compared to three-dimensional perovskites, the shape of the spacer cation is still subject to limitations due to the size of the inorganic pocket between four adjacent corner-sharing octahedra. To investigate the effect of the spacer cation branching on the formation of Ruddlesden−Popper (RP) structures, we performed a comprehensive investigation of structures formed using tert-butyl ammonium (t-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 108 publications
3
19
0
Order By: Relevance
“…The optical measurements indicated that synthesis starting from a one-to-one iodide-bromide stoichiometry results in t-BA 2 PbBr 2 I 2 , a crystallized n = 1 RP phase, while syntheses starting from pure bromide or pure iodide stoichiometries do not yield Q2DP structures. 22 We confirmed the instability of the pure halide Q2DPs by calculating the formation energies of the global minima found with GO-MHALP as well as by XRD measurements.…”
Section: (4amp)pbbrsupporting
confidence: 70%
See 4 more Smart Citations
“…The optical measurements indicated that synthesis starting from a one-to-one iodide-bromide stoichiometry results in t-BA 2 PbBr 2 I 2 , a crystallized n = 1 RP phase, while syntheses starting from pure bromide or pure iodide stoichiometries do not yield Q2DP structures. 22 We confirmed the instability of the pure halide Q2DPs by calculating the formation energies of the global minima found with GO-MHALP as well as by XRD measurements.…”
Section: (4amp)pbbrsupporting
confidence: 70%
“…We confirmed that not only the specific halide distribution was correctly predicted by GO-MHALP, but also that the structural details were predicted very precisely. 22 While the accuracy of the classical potential itself can be significantly improved, within our method it is not necessary for it to be extremely precise. We have shown that the sufficient condition for a very accurate prediction is only that the global minimum of the potential is connected to the DFT global minimum by a DFT local relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations